2019
DOI: 10.1002/mc.23086
|View full text |Cite
|
Sign up to set email alerts
|

Activating transcription factor 1 promoted migration and invasion in lung cancer cells through regulating EGFR and MMP‐2

Abstract: Lung cancer is among the most frequently occurring cancers and the leading cause of cancer‐related deaths worldwide. Nonsmall cell lung cancer is accountable for 85% to 90% of all lung cancer cases and develops distant metastases with high mortality. In this work, we elucidated the role of activating transcription factor 1 (ATF1) in migration and invasion of lung cancer cells. We found that the migration and invasion were inhibited with ATF1 silencing in lung cancer cells. By contrast, ATF1 overexpression led … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Activated transcription factor 1 (ATF1) plays an important role in the migration and invasion of lung cancer cells. A study proposed that the silencing of ATF1 can induce the down-regulation of MMP2 expression, thereby inhibiting the migration and invasion of lung cancer cells [ 23 ]. Recent publications and clinical trials have emphasized the potential value of measuring circulating or tissue MMP-2 levels as a tool for tumor diagnosis or prognosis prediction, or as a primary therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…Activated transcription factor 1 (ATF1) plays an important role in the migration and invasion of lung cancer cells. A study proposed that the silencing of ATF1 can induce the down-regulation of MMP2 expression, thereby inhibiting the migration and invasion of lung cancer cells [ 23 ]. Recent publications and clinical trials have emphasized the potential value of measuring circulating or tissue MMP-2 levels as a tool for tumor diagnosis or prognosis prediction, or as a primary therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…Our most significant findings at 24 hours include that GREM2 mutant cells (T allele) migrated less/slower and proliferated less than those with the reference allele; whereas ATF1 T allele‐transfected cells presented increased cell migration and proliferation when compared to the C allele. In this context, numerous studies showed that ATF1 overexpression resulted in increased cell proliferation in various cancers 20,32,33 . However, those effects seem to be site‐specific, as other studies demonstrate that ATF1 might also act as a tumour suppressor such as in breast cancer 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of ATF1 in nasopharyngeal carcinoma was positively correlated with the expression of MMP2. ATF1 led to the increasing level of MMP2 expression as well as promotion in lung cancer cell migration and invasion [ 38 ]. However, previous study did not show which phosphorylated site of ATF1 was important for the regulation.…”
Section: Discussionmentioning
confidence: 99%